Resilience, depression and their effect on nurse retention: a survey in rural Indonesia - Ika Buntoro; Conrad Folamauk; Rr Listyawati Nurina; Simon Kleden; Nicholas Handoyo (James Cook University, 2023)
Introduction: Health professionals' maldistribution and retention in underserved areas are global problems. Burnout drives health professionals to leave rural areas. Chronic burnout is linked to depression, and nurses have a higher risk for depression than the general population. Studies suggest that increasing resilience may reduce depression. However, little is known about the effect of resilience on nurses' depression and their rural retention. This study aims to understand the impact of resilience and depression on nurses' retention in rural areas.Methods: An online cross-sectional survey on registered nurses was conducted in July - August 2021 in a rural province in Indonesia. The survey measured the nurses' resilience, depression level, and work duration.Results: A total of 1050 participants joined the study. The results suggest that resilience in nurses is negatively correlated to depression and retention. The mildly depressed group had the shortest retention. There was no difference in the work duration, depression, and resilience scores between the underserved and non-underserved regencies in the province.Discussion: Although not all our hypotheses are supported, some interesting results were obtained. In a previous study, the more senior the doctor, the higher the resilience; in this nurse analysis, the opposite was true - senior nurses were the least resilient. As found in other studies, resilience is negatively correlated to depression. So, resilience training may still benefit the depressed group.Conclusion: Improvement of health professionals' rural retention requires approaches tailored to each profession. Resilience training may be beneficial to retain nurses through mild depression treatment. Keywords: depression, nurse, resilience, rural retention, Indonesia.